Peran Bunyi Dalam Bidang Kedokteran - Apriansyah, Wira; Hayuningrum, Erlian Adi; Candra, Salisa Rizky; Kurniawati, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sound in physics is a longitudinal wave that propagates through a certain medium. Sound occurs due to a vibration, thus creating a sound system that makes the sound audible to the human sense of hearing. The world of medicine continues to experience innovation, and one of the unexpected breakthroughs came from the field of sound, which is the domain of physics. This article uses qualitative methods with data collection and analysis techniques carried out by searching for literature studies through several books, scientific articles and other trusted sources. Sound is a longitudinal type of mechanical wave that propagates and its source is a vibrating object. Sound waves are divided into three, namely, infrasonic, audiosonic and ultrasonic. As is well known, in the medical field, ultrasonic waves are often used. These waves are often used in ultrasound or ultrasonography. However, ultrasonic waves which are useful for the medical field still have many shortcomings